2015
DOI: 10.1016/j.brat.2015.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Emphasizing Malleability in the biology of depression: Durable effects on perceived agency and prognostic pessimism

Abstract: Biological attributions for depression, which are currently ascendant, can lead to prognostic pessimism—the perception that symptoms are relatively immutable and unlikely to abate (Kvaale, Haslam, & Gottdiener, 2013; Lebowitz, Ahn, & Nolen-Hoeksema, 2013). Among symptomatic individuals, this may have important clinical ramifications, as reduced confidence in one’s own ability to overcome depression carries the risk of becoming a self-fulfilling prophecy. Previous research (Lebowitz, Ahn, et al., 2013) has demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 27 publications
0
44
1
Order By: Relevance
“…Moreover, in the present work, an approach that has been shown to mitigate genetic attributions’ detrimental effects on people’s feelings of agency in confronting their symptoms(Lebowitz & Ahn, 2015; Lebowitz et al, 2013) failed to counteract the effects of genetic feedback on symptom recall. This may reflect the fact that overall, the widespread bias toward assuming that genes affect health deterministically is difficult to counteract; indeed, much of the existing work that has effectively weakened such assumptions has done so by disproportionately emphasizing the role of non-genetic factors, which may be viewed as more controllable (Heine et al, 2017).…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Moreover, in the present work, an approach that has been shown to mitigate genetic attributions’ detrimental effects on people’s feelings of agency in confronting their symptoms(Lebowitz & Ahn, 2015; Lebowitz et al, 2013) failed to counteract the effects of genetic feedback on symptom recall. This may reflect the fact that overall, the widespread bias toward assuming that genes affect health deterministically is difficult to counteract; indeed, much of the existing work that has effectively weakened such assumptions has done so by disproportionately emphasizing the role of non-genetic factors, which may be viewed as more controllable (Heine et al, 2017).…”
Section: Discussioncontrasting
confidence: 55%
“…In work by Lebowitz and Ahn (2015), this brief video successfully restored feelings of agency over depression, even among people who strongly attributed depression to biological causes (see also Lebowitz et al, 2013 for similar findings). Thus, if genetic determinism were to cause increased recall of depressive symptoms, this video intervention could have counteracted such an effect.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…A more tolerant, less dichotomous and rigid, separation of ill and healthy could be associated with an improved sense of perceived personal control (e.g., Lebowitz & Ahn, 2015), In a recent series of studies using unselected community samples, Greenaway et al (2015) found robust positive associations between group identification and perceived personal control. They theorized an upward spiral of well-being, whereby feelings of control increase as individuals identify with groups, which in turn allows individuals to increase the quantity and quality of their social connections.…”
Section: Discussionmentioning
confidence: 99%